Prevalence of chronic kidney disease in fabry disease patients: Multicenter cross sectional study in Argentina - Sebastián Jaurretche (Molecular Genetics and Metabolism Reports, 2017)
Nephropathy is one of the major complications of Fabry Disease (FD) and mainly includes reduced glomerular filtration rate (GFR) and proteinuria. Despite the frequency, scarce information exists regarding the frequency of CKD as well as other related complications in FD patients in Argentina. The aim of the study was to measure the prevalence of CKD at diagnosis of FD as well as to describe other related conditions in a large cohort of patients with FD. Methods: a cross-sectional study performed in three FD centers of Argentina during January 2014 and January 2016. Information at diagnosis regarding patient demographics, disease characteristics, key laboratory values, and renal, cardiac, cerebrovascular diseases and other related complications were collected. Results: A total of 60 patients were included. The mean age at diagnosis was 25.5 ± 16 years. 42% of included patients presented CKD in which the disease was mild (GFR ≥60 and <90) in 60% (n = 15), moderate (GFR ≥30 and <60) in 16% (n = 4), severe (GFR ≥15 and <30) in 4% (n = 1) and failure (GFR <15) in 20% (n = 5). Arrhythmias were reported for 13.3% of patients. In 33.3% the echocardiographic evaluation demonstrated left ventricular hypertrophy and peripheral neuropathy in 63.3%. Conclusion: This study presents information regarding the prevalence of CKD in a large cohort of FD patients at the moment of diagnosis in Argentina. Future studies will help us to confirm these initial findings.